Numerical Study of a Supersonic Nozzle Gas Jet Laden with a Dry Powder Fire-extinguishing Agent Injected from a Bypass Injector - L. Zhang; S. Wu; Y. Feng; H. Guan (Journal of Applied Fluid Mechanics)
To enhance the firefighting capabilities of traditional dry powder extinguishers, we incorporated an air-assisted supersonic nozzle, which is simulated using Euler-Lagrange interphase coupling to simulate the injection of firefighting agents into a supersonic, two-dimensional axisymmetric gas flow from a bypass injector. During the simulation, we employed our newly developed modified drag coefficient model, capable of accommodating a broad spectrum of particle Reynolds and Mach number conditions. Parameter studies show that an increase in the injector position, angle, and total pressure ratio generally causes a decrease in the average particle velocity vp,a, and an increase in the dispersion Ψp and velocity unevenness Φvp; an increase in the total pressure ratio of the main nozzle leads to an increase in Φvp and vp,a. However, under specific conditions, the monotonic dependency upon these parameters may be disrupted. For example, the performance indicators at the position of the injector near the nozzle throat and a larger total injector pressure ratio, as well as vp,a at smaller injection angles and Ψp at larger injection angles, may run counter to the monotonicity.